Driving Innovation in Service Organisations A Study in the German Airport Industry - Scheler, Jessica; SpringerLink (Online service) (Wiesbaden : Gabler Verlag : Imprint: Gabler Verlag, 2013)
With an ever increasing globalization of the economy, rapid technological progress, and intensifying competition, service firms such as airports constantly have to fuel the engine of renewal to keep on prospering. Nevertheless, research is still left with the critical question how service firms can manage their ability to innovate. By applying a resource perspective, Jessica Scheler explores drivers and barriers affecting the ability to innovate in the airport industry. Findings reveal significant categories and deliver valuable findings for academia and managerial practice particularly with regard to leadership issues, organizational structure, and roles of individuals.  .
Systematic Review of the Service Dominant Logic-Literature -- Opportunities and challenges for the German Airport Industry -- Drivers and barriers influencing the ability to innovate in service organizations. -Typology of innovation opponents.
Keywords: Market research; Market Research/Competitive Intelligence